2016
DOI: 10.4172/2161-069x.1000441
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Encephalopathy; Prevalence, Precipitating Factors and Challenges of Management in a Resource-Limited Setting

Abstract: Background and Aims: Hepatic encephalopathy, a neuropsychiatric syndrome caused by portosystemic venous shunting, clinical presentation ranges from minimal to overt H.E. It is a common complication of advanced liver disease with significant morbidity and mortality The aim of this study was to assess the prevalence, common precipitating factors, and outcomes of hepatic encephalopathy in patients with preexisting liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
5
7
0
Order By: Relevance
“…With regards to severity of cirrhosis assessed by CTP scores, 87.38% of our study subjects fell under class C. In the study by Nayak M et al 9 also, majority (60 %) were in Class C followed by 24 % in Class A and only 16 % in Class B. Similarly Raphael KC et al 15 also reported that 77.3% of their subjects had class C CTP score. Hepatic encephalopathy (HE) is a major complication of endstage liver disease and acute liver failure.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…With regards to severity of cirrhosis assessed by CTP scores, 87.38% of our study subjects fell under class C. In the study by Nayak M et al 9 also, majority (60 %) were in Class C followed by 24 % in Class A and only 16 % in Class B. Similarly Raphael KC et al 15 also reported that 77.3% of their subjects had class C CTP score. Hepatic encephalopathy (HE) is a major complication of endstage liver disease and acute liver failure.…”
Section: Discussionsupporting
confidence: 51%
“…In our study, most of the subjects (56.31%) were aged between 41 to 60 years with the mean age of the study population at 49.58 (± 12.26) years. The mean age of the subjects was also 47 years in the study by Raphael KC et al15 45.63 % of our study subjects stayed in the hospital between 1 week to 3 weeks. Similarly Iqbal J et al 14 also reported a mean hospital stay duration of 11 days in their study.…”
supporting
confidence: 64%
“…Infections, constipation, and gastrointestinal bleeding were identified as the major precipitants of HE in the study conducted by Mumtaz et al [30], in Pakistan. Commonly observed precipitating factors of HE by Raphael et al [31] were the use of diuretics in massive ascites, infections, and GI bleeding. Literature from developed countries, however, has not identified infections among the most common precipitating events [32]; this probably reflects the hygienic, nutritional, and immune status in their patients.…”
Section: Discussionmentioning
confidence: 98%
“…These manifestations are due to acute or chronic liver failure [ 1 ]. HE affects 45-70% of patients with liver cirrhosis and 10-20% of patients with Transjugular Porto Systemic Shunts, in developed countries [ 2 ]. HE causes hospitalization and high rates of mortality as a result of end-stage liver disease, reaching to coma [ 3 ].…”
Section: Introductionmentioning
confidence: 99%